Stress Adaptive Plasticity: Aegilops tauschii and Triticum dicoccoides as Potential Donors of Drought Associated Morpho-Physiological Traits in Wheat - Suneja, Yadhu; Gupta, Anil Kumar; Bains, Navtej Singh (Frontiers in Plant Science, 2019)
The inconsistent prevalence of abiotic stress in most of the agroecosystems can be addressed through deployment of plant material with stress adaptive plasticity. The present study explores water stress induced plasticity for early root-shoot development, proline induction and cell membrane injury in fifty seven accessions of Aegilops tauschii (DD-genome) and twenty six accessions of Triticum dicoccoides (AABB-genome) along with durum and bread wheat cultivars. Thirty three Ae. tauschii accessions and eighteen T. dicoccoides accessions showed an increase in root dry weight (ranging from 1.8% to 294.75%) under water stress. Shoot parameters- length and biomass, by and large were suppressed by water stress, but genotypes with stress adaptive plasticity leading to improvement of shoot traits (e.g., Ae tauschii accession 14191 and T. dicoccoides accession 7130) could be identified. Water stress induced active responses, rather than passive repartitioning of biomass was indicated by better shoot growth in seedlings of genotypes with enhanced root growth under stress. Membrane injury seemed to work as a trigger to activate water stress adaptive cellular machinery and was found positively correlated with several root-shoot based adaptive responses in seedlings. Stress induced proline accumulation in leaf tissue showed marked inter- and intra-specific genetic variation but hardly any association with stress adaptive plasticity. Genotypic variation for early stage plasticity traits viz., change in root dry weight, shoot length, shoot fresh weight, shoot dry weight and membrane injury positively correlated with grain weight based stress tolerance index (r = 0.267, r = 0.404, r = 0.299, r = 0.526 and r = 0.359 respectively). In another such trend, adaptive seedling plasticity correlated positively with resistance to early flowering under stress (r = 0.372 with membrane injury, r = 0.286 with change in root length, r= 0.352 with change in shoot length, r = 0.268 with change in shoot dry weight). Overall, Ae. tauschii accessions 9816, 14109, 14128 and T. dicoccoides accessions 5259 and 7130 were identified as potential donors of stress adaptive plasticity. The prospect of the study for molecular marker tagging, cloning of plasticity genes and creation of elite synthetic hexaploid donors is discussed.